Sustainable development, global trade and social rights - Perulli, Adalberto, 1961-; Treu, Tiziano (Studies in employment and social policy ;, 2018)
"Three major fields of international law - trade, the environment, and human rights - have become inextricably intertwined in today's world. A practitioner, policymaker, businessperson, or academic involved in any one of these fields must now be conversant with the other two. This groundbreaking book considers the crucial elements of this complex engagement, with eleven authoritative discussions by some of the most important and widely renowned professors of labor, commercial, and international law and experts from the International Labour Organization and the International Society for Labour and Social Security Law. Focusing primarily on the "social pillar" of sustainability, the authors cover such critical issues as the following: - the "creeping de-globalization" manifested by Brexit and US protectionist policies; - new and renegotiated multilateral "mega" treaties; - prospects for effectively codifying social responsibilities of multinational corporations; - nexus of economic comparative advantage and excessive exploitation of natural resources; - weak (or non-existent) enforcement of labor clauses in trade agreements; - assessing and managing environmental and social risk in project finance; and - stabilization clauses in state-investor agreements. An analysis of MERCOSUR serves as a revealing insight into the differences between trade agreements concluded among developing countries and those concluded among developed countries. A much-needed probing of the future of global trade in the light of a resurgence of economic nationalisms, this book takes a giant step towards a new consensus and cohesion phase in the international community where development policies, international business transactions, and social and environmental sustainability coexist harmoniously."-- Wolters Kluwer CCH Website.